Investigating the Anticancer Potential of Salvicine as a Modulator of Topoisomerase II and ROS Signaling Cascade - Dey, Dipta; Hasan, Mohammad Mehedi; Biswas, Partha; Papadakos, Stavros P.; Rayan, Rehab A.; Tasnim, Sabiha; Bilal, Muhammad; Islam, Mohammod Johirul; Arshe, Farzana Alam; Arshad, Efat Muhammad; Farzana, Maisha; Rahaman, Tanjim Ishraq; et al. (Frontiers in Oncology, 2022)
Salvicine is a new diterpenoid quinone substance that was made by changing the structure of a compound from natural source found in a Chinese herb. It has powerful growth-controlling abilities against a broad range of human cancer cells in both the in vitro and in vivo environment. A significant inhibitory effect of salvicine on multidrug-resistant (MDR) cells has also been discovered. To better understand salvicine's anticancer effects on human topoisomerase II, as well as the putative binding domains and molecular interactions, several research studies have been examined the activities of salvicine on topoisomerase II by inducing ROS signaling. In opposition to the well-known topoisomerase II toxin etoposide, several enzymatic experiments revealed that salvicine mostly decreases catalytic activity with a negligible DNA breakage effect (VP16). Interestingly, salvicine dramatically reduced lung metastatic formation in MDA-MB-435 orthotopic lung cancer cell line. Recent investigations established that salvicine is a new non-intercalative topoisomerase II toxin by interacting to the ATPase domains, increasing DNA- topoisomerase II interaction, and suppressing DNA relegation and ATP hydrolysis. In addition, investigations have revealed that salcivine-induced ROS plays a critical role in the anticancer-mediated signaling pathway, involving topoisomerase II suppression, DNA damage, overcoming MDR, and tumor cell adhesion suppression, among other things. In this comprehensive review study, we have briefly demonstrated the role of salvicine for regulating the ROS signaling pathway, DNA damage response (DDR) in suppressing the cancer cell progression. We have depicted the mechanism of Action of salvicine in suppressing topoisomerase II through the ROS induction. We have also depicted the inhibitory mechanism of several oncogenic pathways by salvicine. Consequently, it is hypothesized that salvicine has potential inhibitory activity on the DNA topoisomerase II complex through the induction of ROS, that in response has effective anticancer properties.